Comparative Outcomes of Surgery and Chemoradiotherapy After Neoadjuvant Chemotherapy in Stage II–III Bladder Cancer - Bayram, Doğan; Bal, Öznur; Türkel, Alper; Sekmek, Serhat; Hafızoğlu, Emre; Karabuga, Berkan; Doğan, Mutlu; Algın, Efnan; Uncu, Doğan (The European Research Journal, 2026)
Objectives: Radical cystectomy following neoadjuvant chemotherapy is the standard treatment for Muscle-Invasive Bladder Cancer (MIBC). However, definitive chemoradiotherapy may represent a viable alternative in patients who are medically inoperable or decline surgery. This study aimed to compare the clinical outcomes of patients with stage II–III MIBC treated with neoadjuvant chemotherapy followed by either Radical cystectomy or CRT, the latter performed without maximal transurethral resection of bladder tumor (TURBT). Methods: This retrospective study included 63 patients with stage II–III MIBC treated between December 2014 and March 2025 at two tertiary referral centers in Türkiye. All patients received neoadjuvant chemotherapy (NAC) prior to either surgery (n=39) or Chemoradiotherapy (CRT) (n=24). Clinicopathological, laboratory, and survival data were analyzed. Overall Survival (OS) and Event-Free Survival (EFS) were assessed using the Kaplan–Meier method and compared with the log-rank test. Cox regression was used to identify independent prognostic factors. Results: The median age was 64 years, and 88.9% of patients were male. Comorbidities were more frequent in the CRT group (79.2% vs. 59%), though the difference was not statistically significant (P=0.099). Median OS was 46.5 months in the surgery group and 31.6 months in the CRT group (P=0.407), while median EFS was 30.1 and 21.0 months, respectively (P=0.375). Distant metastasis was the most common recurrence pattern (36.5%). Multivariate analysis identified comorbidity (Hazard ratio [HR] = 0.37, 95% CI: 0.17–0.80, P=0.012) and hemoglobin